Tonghua Liyan granules in the treatment of Laryngopharyngeal reflux disease with stagnation of phlegm and qi syndrome: a randomized, double-blind, placebo-controlled study - Li, Yading; Zheng, Mingxian; Wang, Yi; Xu, Gaofan; He, Yunyun; Wu, Yue; Wang, Xiao; Liu, Yuyang; Jiang, Yujie; Liu, Xiaowen; Meng, Yangyang; Yap, Yixuan; et al. (Frontiers in Pharmacology, 2024)
Background: Laryngopharyngeal reflux disease (LPRD) is an extraesophageal syndromic manifestation of gastroesophageal reflux disease (GERD). Despite the increasing incidence of and concern about LPRD, treatment with proton pump inhibitors (PPIs) is unsatisfactory. Here, LPRD was treated with Tonghua Liyan (THLY) granules in combination with PPIs to evaluate treatment efficacy and possible adverse reactions. Methods: Seventy-six LPRD patients with stagnation of phlegm and qi syndrome (SPQS) were randomly divided into an experimental group and a control group. The experimental group received THLY granules combined with rabeprazole capsules. The control group received THLY granule placebo combined with rabeprazole capsules. A parallel, randomized, double-blind, placebo-controlled clinical trial was conducted with these two groups. The treatment cycle was 8 weeks. The reflux symptom index (RSI), clinical symptom score, salivary pepsin content, reflux finding score (RFS) and gastroesophageal reflux disease questionnaire (GerdQ) were used to evaluate clinical efficacy. The final efficacy rate was evaluated according to the RSI and clinical symptom score. Results: Compared with those at baseline, all the indicators in the experimental group and control group significantly improved (p < 0.01). In terms of the RSI, clinical symptom score, and RFS, the experimental group had a higher degree of improvement (p < 0.05), and the overall efficacy rate was higher (p < 0.05). In terms of the salivary pepsin concentration and GerdQ, there was no significant difference between the test group and the control group (p > 0.05). Both groups of safety indicators showed no abnormalities and did not cause any allergic reactions in the body. Conclusion: Compared with PPIs alone, THLY granules combined with PPIs are more effective in the treatment of LPRD patients with SPQS in terms of symptoms and signs. This combination treatment, because of its higher clinical efficacy and lack of obvious adverse reactions, is worthy of clinical promotion and further in-depth study. Clinical Trial Registration:www.chictr.org.cn, identifier ChiCTR2100046614